Begonia obdeltata (Begoniaceae), a new species from northeast Brazil - Gregório, Bernarda De Souza Gregório; Jacques, Eliane De Lima; Costa, Jorge Antonio Silva; Rapini, Alessandro (Phytotaxa, 2014)
Begonia obdeltata, a new species of Begoniaceae from northeast Brazil, is described and illustrated. It is similar to B. grisea and B. petasitifolia, with which it is compared. Diagnostic characters, geographic distribution and conservation status of the new species are presented.